2019
DOI: 10.1051/e3sconf/201911102013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort and draught assessment in a modern open office building in Tallinn

Abstract: Modern office building users have high expectations about the working environment and thermal comfort, which requires the installation of complex technical systems such as combined cooling and ventilation. Room conditioning units of these systems must ensure temperature and ventilation control in a way that air velocity is low and the air temperature in acceptable range. Achieving air distribution avoiding draught is one of the key elements of a thermal comfort in modern office landscape. Higher air velocity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Thermal comfort constitutes a central topic in the management of modern buildings, as it is closely related to the well-being of tenants; in office buildings, this is also strictly related to the productivity of employees [1], [2]. One of the biggest sources of complaint from the occupants in working areas consists of indoor air temperature fluctuations, thermal asymmetry and draught of cold air near the windows [2]. The latter is generally defined as air movement that induces an unwanted cooling effect on the body [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal comfort constitutes a central topic in the management of modern buildings, as it is closely related to the well-being of tenants; in office buildings, this is also strictly related to the productivity of employees [1], [2]. One of the biggest sources of complaint from the occupants in working areas consists of indoor air temperature fluctuations, thermal asymmetry and draught of cold air near the windows [2]. The latter is generally defined as air movement that induces an unwanted cooling effect on the body [3].…”
Section: Introductionmentioning
confidence: 99%
“…A typical solution for contrasting the formation of such downdraught is positioning heat emitters such as radiators or convectors under the window, however this does not eliminate the problem per se. Unfortunately, the most common procedure is overheating the space, with higher supply air temperature than the design value (for instance, 21°C instead of 17°C) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The latter factors also increase the risk of draught in occupied spaces. In several studies, draught rate (DR) has been identified as the main cause of discomfort even if other thermal environment factors are at satisfactory levels [6,15,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, the authors suggested a more careful design of the ventilation systems in classrooms. Recently, Kiil et al [15] reported their assessment of the draught and thermal comfort in an office building. It was found that DR was below 10% in heating and transient period measurements, but the risk of draught was assessed for the intensive cooling mode.…”
Section: Introductionmentioning
confidence: 99%